Effect of information, education, and communication activity on health literacy of obesity and physical activity among school-going adolescents in Delhi - Srishti Yadav; Anita Khokhar (Wolters Kluwer Medknow Publications, 2020)
Introduction: Awareness about risk factors of lifestyle diseases such as obesity and lack of physical activity is present among adolescents but to some extent only. Furthermore, younger ones tend to maintain the unhealthy habits as they age. Thus, intervention should start at an early age. Aim: This study was conducted to assess the health literacy of school-going adolescents regarding obesity and lack of physical activity as risk factors for lifestyle diseases and assess the improvement in their knowledge after different information, education and communication (IEC) activities in two schools. Settings and Design: It was a school-based interventional study conducted in two schools. Material and Methods: Pretested questionnaire for baseline and post-IEC activity assessment of health literacy of risk factors like obesity and physical inactivity in lifestyle diseases was administered among students of Class 6, 7, and 8. Postintervention data were collected at 2 weeks after the first intervention and 3 months after the last intervention. Responses were scored and categorized as satisfactory and unsatisfactory. Statistical Analysis: Chi square test was applied to compare the proportion of scores (satisfactory and unsatisfactory) at baseline, 2 weeks and 3 months. Results: About 64% students in school 1 and 69% students in school 2 knew what obesity was. Moreover, about 79% of students in school 1 and 69% students in school 2 knew the minimum duration of physical activity required to prevent lifestyle diseases. There were a higher proportion of students with a satisfactory level of knowledge in both the schools after 2 weeks and 3 months of IEC activity, and the differences were statistically significant (P < 0.05). Conclusion: The proportion of students having satisfactory knowledge satisfactory knowledge of obesity and physical activity increased after educational interventions among school-going adolescents of both the schools.